(untitled) (CIPEEX, 2022)
THE PURPOSE OF THE STUDY WAS TO ASSESS WHETHER THERE ARE DIFFERENCES IN CARDIORESPIRATORY FITNESS BETWEEN CHILDREN WITH AND WITHOUT CYSTIC FIBROSIS (CF). TEN CHILDREN WITH CF ATTENDED AT A REFERRAL CENTER FOR THE TREATMENT OF CF AND 13 CHILDREN WITHOUT CF WERE EVALUATED. THE AVERAGE AGE OF THE CHILDREN WITH CF WAS 10.40 (3.13) YEARS AND THOSE WITHOUT CF WAS 9.39 (3.25) YEARS. THE CHILDREN PERFORMED THE THREE-MINUTE STEP TEST WITH MONITORING OF HEMODYNAMIC PARAMETERS AND THE RATING OF PERCEIVED EXERTION (RPE) EVERY MINUTE. OXYGEN DESATURATION OF 4% DURING THE TEST OCCURRED IN THREE CHILDREN WITH CF AND NONE OF THE CHILDREN REACHED A SATO2 PERCENTAGE < 75%. AFTER THE STEP TEST, THE FINDINGS SHOWED THAT CHILDREN WITH CF PRESENTED HIGHER RPE SCORES DURING THE TEST (P = 0.002) WHEN COMPARED TO CHILDREN WITHOUT CF (P < 0.001). THE RPE WAS THE ONLY PARAMETER THAT CHANGED DURING THE TEST AND DEMONSTRATED THAT CHILDREN WITH CYSTIC FIBROSIS TIRED MORE DURING THE TEST WHEN COMPARED TO CHILDREN WITHOUT CF DESPITE THE LACK OF CHANGES IN HEMODYNAMIC VARIABLES.